Basic Sciences. Basis of Clinical Medicine. - Jaime Hinzpeter (International Physiology Journal, 2018)
A short editorial underscores the bridge between basic sciences and clinical medicine. It emphasizes how mechanistic knowledge informs diagnostics and therapy, and calls for curricula that strengthen this continuum.